(untitled) (Research, Society and Development, 2022)
Objective: to understand the stressors, reaction and parental interaction of children undergoing outpatient chemotherapy treatment in relation to home care. Method: a comprehensive study, with a qualitative approach, carried out with fourteen fathers and mothers of children undergoing outpatient chemotherapy treatment at a specialized hospital. Data collection took place through a focus group from January to February 2018. Data were submitted to content analysis proposed by Bardin and discussed according to Betty Neuman’s Systems Model. Results: three thematic categories were created: 1. Stressors: taking care of the child at home after outpatient chemotherapy; 2. Interaction with the environment: living with cancer and outpatient chemotherapy treatment; and 3. Parents’ reaction: overcoming having a child with cancer and undergoing outpatient chemotherapy treatment. Conclusion: for parents, living with cancer, chemotherapy treatment and providing care to the child at home involves suffering and uncertainties. This experience is permeated by stressors in terms of changes in family dynamics and structure, lack of autonomy to play their parental role and insecurity regarding home care. The interaction with the oncopediatric universe allows parents to experience social stigmas of the disease and suffer intense psychological shock and emotional imbalance. However, this experience is softened when parents are faced with the humanization of the health team and with the solidarity of other parents who experience a similar situation, at this moment, parents find strength to face and overcome difficult times.